(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Intestinal injury may result from motor vehicle accidents, industrial accidents, gunshot, and stab injuries. However, damage to the abdomen’s hollow organs, especially the sigmoid colon, following blunt abdominal trauma is uncommon. The literature does not commonly report a transaction or perforation of the sigmoid colon. We are writing a fatal case of sigmoid colon transaction due to blunt abdominal trauma and the underlying mechanism of perforation of the sigmoid colon. We identified the exact cause of death. The probable mechanism of perforation of the sigmoid colon is the crushing force between the vehicle and the pelvis.